U.S. NATIONAL MISSILE DEFENSE DEPLOYMENT IN THE ASIA-PACIFIC REGION - J. Y. Parshkova (Vestnik MGIMO-Universiteta, 2015)
The article analyses military and technical cooperation of the United States and APAC. After the successful implementation of the first phase of the European Phased Adaptive Approach (EPAA), adopted in September 2009, the United States began to develop a similar plan for the Asia-Pacific region - Asia-Pacific Adaptive Approach. The ultimate goal of such large-scale missile defense deployment is to convince the adversaries that the use of ballistic missiles is useless in military terms and that any attack on the United States and its allies is doomed to failure. The United States are developing military cooperation with its allies and partner countries in the Asia-Pacific region, excluding interests of China and Russia. That may only exacerbate a struggle for power between the three world largest countries and lead to negative consequences - involvement in the arms race.